Cover Image, Volume 233, Number 4, April 2018. Issue 4 (22nd December 2017) - Hertig, Vanessa; Matos‐Nieves, Adrianna; Garg, Vidu; Villeneuve, Louis; Mamarbachi, Maya; Caland, Laurie; Calderone, Angelino
Abstract : Cover : The cover image, by Hertig et al., is based on the Original Research Article, Nestin expression is dynamically regulated in cardiomyocytes during embryogenesis, DOI:10.1002/jcp.26165 .